Neuromodulation With Thoracic Dorsal Root Ganglion Stimulation Reduces Ventricular Arrhythmogenicity - Kuwabara, Yuki; Salavatian, Siamak; Howard-Quijano, Kimberly; Yamaguchi, Tomoki; Lundquist, Eevanna; Mahajan, Aman (Frontiers in Physiology, 2021)
Introduction: Sympathetic hyperactivity is strongly associated with ventricular arrhythmias and sudden cardiac death. Neuromodulation therapies provide therapeutic options for ventricular arrhythmias by modulating cardiospinal reflexes and reducing sympathetic output at the level of the spinal cord. Dorsal root ganglion stimulation (DRGS) is a recent neuromodulatory approach, however, its role in reducing ventricular arrhythmias has not been evaluated. The aim of this study was to determine if DRGS can reduce the cardiac sympathoexcitation and ventricular arrhythmogenicty induced by programmed ventricular extrastimulation. We further evaluated the efficacy of thoracic DRGS at both low (20-Hz) and high (1k-Hz) stimulation frequencies. Methods: Myocardial stress and cardiac sympathoexcitation was induced in Yorkshire pigs (n=8) with ventricular extrastimulation (S1/S2 pacing), before and after DRGS. A DRG stimulating catheter was placed at the left T2 spinal level and animals were randomized to receive low frequency (20-Hz and 0.4 ms) or high frequency (1k-Hz and 0.03 ms) DRGS at 90 % of motor threshold for 30 minutes. High-fidelity cardiac electrophysiology recordings were performed with an epicardial electrode array measuring activation recovery intervals (ARI), electrical restitution curve (Smax) and Tp-Te interval. Results: DRGS, at both 20-Hz and 1k-Hz, decreased S1/S2 pacing-induced ARI shortening (20-Hz DRGS -217 ms, Control -509 ms, P=0.007; 1k-Hz DRGS -132 ms, Control -468 ms, P=0.001). DRGS also reduced arrhythmogenicity as measured by decrease of Smax (20-Hz DRGS 0.50.07, Control 0.70.04, P=0.006; 1-kHz DRGS 0.50.04, Control 0.70.03, P=0.007), and decrease of Tp-Te interval/QTc (20-Hz DRGS 2.70.13, Control, P=0.001; 1k-Hz DRGS 2.80.08, Control; 3.10.03, P=0.007). Conclusions: In a porcine model, we show that thoracic DRGS decreased cardiac sympathoexcitation and ventricular arrhythmogencity with programmed ventricular extrastimulation. In addition, we demonstrate that both low and high-frequency DRGS can be effective neuromodulatory approaches for reducing cardiac excitability during sympathetic hyperactivity.